2014
DOI: 10.5586/asbp.2002.013
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglucose isomerase (PGI) polymorphism in Sorbus torminalis (L.) Crantz

Abstract: Dormant buds of individual Sorbus torminalis trees collected from eight Polish populations were tested with horizontal gel electrophoresis according to one locus of PGI enzyme system. Three allozymes of different frequency were identified in each population. Genetic variability based on PGI locus A was high within seven populations (mean Ho=0.602 and mean Pg=0.491). Only one population with A3A3 genotypes was monomorphic, most probably due to intensive vegetative propagation or founder effect. The lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…As expected from a largely outbreeding tree, S. torminalis has been found to be genetically diverse within and between populations with strong gene flow (Demesure et al 2000a;Oddou-Muratorio et al 2001aBednorz & Krzakowa 2002;Bednorz, Myczko & Kosi nski 2004Oddou-Muratorio, Klein & Austerlitz 2005;Rasmussen & Kollmann 2004bHoebee et al 2006Hoebee et al , 2007Angelone et al 2007;Espahbodi et al 2008, Jankowska-Wroblewska et al 2016. Sorbus torminalis in Britain has a lower genetic diversity than the other two common sexually reproducing diploid species, S. aria and S. aucuparia (Proctor, Proctor & Groenhof 1989;Chester et al 2007) and lower than S. torminalis in mainland Europe: Chester et al found that pollen exchange shows two main patterns: preferential mating between neighbouring trees from local pollen dispersal with a mean of 6 pollen donors providing the pollen cloud around a given tree, and also long-distance pollen movement of up to 2Á5 km.…”
Section: Floral and Seed Charactersmentioning
confidence: 70%
See 3 more Smart Citations
“…As expected from a largely outbreeding tree, S. torminalis has been found to be genetically diverse within and between populations with strong gene flow (Demesure et al 2000a;Oddou-Muratorio et al 2001aBednorz & Krzakowa 2002;Bednorz, Myczko & Kosi nski 2004Oddou-Muratorio, Klein & Austerlitz 2005;Rasmussen & Kollmann 2004bHoebee et al 2006Hoebee et al , 2007Angelone et al 2007;Espahbodi et al 2008, Jankowska-Wroblewska et al 2016. Sorbus torminalis in Britain has a lower genetic diversity than the other two common sexually reproducing diploid species, S. aria and S. aucuparia (Proctor, Proctor & Groenhof 1989;Chester et al 2007) and lower than S. torminalis in mainland Europe: Chester et al found that pollen exchange shows two main patterns: preferential mating between neighbouring trees from local pollen dispersal with a mean of 6 pollen donors providing the pollen cloud around a given tree, and also long-distance pollen movement of up to 2Á5 km.…”
Section: Floral and Seed Charactersmentioning
confidence: 70%
“…2000a; Oddou‐Muratorio et al . 2001a, , ; Bednorz & Krzakowa ; Bednorz, Myczko & Kosiński , 2006; Oddou‐Muratorio, Klein & Austerlitz ; Rasmussen & Kollmann 2004b, ; Hoebee et al . , ; Angelone et al .…”
Section: Floral and Seed Charactersunclassified
See 2 more Smart Citations